Penurunan Customer Complaint Dengan Mengurangi Flowout di Departemen EBM PT. X - Celia Devita Iskandar; Felecia Felecia (Jurnal Titra, 2019)
Customer who receive defect products can file customer complaint. Rejection customer complaint affect the company the most because it involves product returns. Customer will send defect product to be sorted by PT. X and sent back to customer, which incurring transportation cost, sorting cost, material cost, etc. Customer complaint rate is one of PT. X Quality Department’s target for Key Performance Indicator which must be fulfilled every year. Customer complaint rate must be reduced by 15% of last year’s customer complaint rate. Bottle from EBM Department contributes to 30.8% of customer complaint happened in 2017 and 2018. Root cause of bottle customer complaint will be found using 5 Whys to achieve Quality Department’s KPI goal in 2019. Root cause consist of there is no Work Instruction for selection method, there is no schedule to review Defect Range Board, briefing rarely done to selector and selector lack of training. Suggestions given are selection method based on Work Instruction, schedule for Defect Range Board review, schedule for briefing to selector, training for inspector, jig utilization for all bottle and automated machine to detect defect on dimension. Suggestions implementation will potentially reduce 50% of customer complaint.